Penerapan Data Mining Untuk Analisa Pola Pembelian Produk Menggunakan Algoritma Frequent Pattern – Growth - Soleh, Paisal; Tholib, Abu; Hidayat, M. Noer Fadli (Rekayasa, 2021)
An important aspect of a sales business is the pattern of product purchases, which is one of the supporting factors for increasing revenue, as well as customer arrivals. To find out all aspects of a good buying model, it is measured based on products that customers often buy, products purchased at the same time, usage based on these products, and the relationship between each product. One place of business that seeks to develop a business strategy by using a product purchase pattern is the Avindo Motor Shop. Competition in the business world requires Avindo Motor to improve the quality of sales using a method or method so that what goods are usually purchased by customers can be known. In a day Avindo Motor is not deserted by buyers to make transactions, the resulting transaction data can reach hundreds so that every day the purchase of data. The stages of this research are the literature study stage, data collection stage, data management with data mining, results analysis stage, and presentation stage. From the discussion that the researcher has done, it can be concluded that to determine the pattern of purchasing products using Frequent Pattern Growth has been successfully carried out, and an association rule has been determined at the Avindo Motor store, such as if you buy nuts you will buy clips, if you buy inner tubes you will buy nuts and if you buy an inner tube, you will buy a clip.